TECHNO PSYCHOLOGY IN DISTANCE LEARNING DURING THE COVID-19 PANDEMIC - Failasuf Fadli; Mochamad Iskarim (Program Studi PGSD Universitas Flores, 2022)
The purpose of this article is to describe the results of a psychological review analysis of shifting values in learning using a distance learning system. This article will review the learning process during the COVID-19 pandemic. Some students carry out learning with a feeling of anxiety, because of the fear of contracting Covid-19, which has an impact on the psychology of learning. Unstable motivation, because there is no offline interaction so that the learning process is carried out depending on one's own initiative. Discipline is difficult to implement, because opportunities for many disturbances that cause learning focus and low emotional control when encountering problems with damage and difficulty using technology media. Of these various problems, the need for technology integration as a learning solution is the right step. In uncovering these learning phenomena, this article uses descriptive qualitative research methods. The data collection techniques used were virtual observation techniques and online interviews, then the data were analyzed using the Mils and Huberman method. The results of this study, the authors try to offer a new alternative with the term Techno-psychology as an integrated product between the use of technology in distance learning and psychology on motivation, self-discipline, and emotion.